Menelanjangi Mens Rea Sendenbu: Analisis Linguistik Forensik terhadap Tindak Tutur Komisif Manipulatif pada Slogan “Nippon Cahaya, Pelindung dan Pemimpin Asia” - Arsyiatin Arroby (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
This research deconstructs the manipulative architecture in the propaganda trilogy of the Japanese Army in 1942, namely Nippon Tjahaja Asia, Nippon Pelindoeng Asia, and Nippon Leader Asia, which have often been reduced to mere political euphemisms. With a descriptive-qualitative design, this study integrates Malcolm Coulthard and Alison Johnson's parameter-based Forensic Linguistics as the grand theory, as well as the three-dimensional model of Norman Fairclough's Critical Discourse Analysis (AWK) as an operational analysis instrument. The results of the analysis show that lexical manipulation through the messianic triptych "Light, Protector, Leader" and the use of assertive clauses without copula are engineered to produce false consciousness. Forensic Linguistic Parameters confirm the existence of a planned mens rea (malicious intent) from Sendenbu, with an extreme disparity between commissive speech in the form of a promise of protection and military actus reus in the form of romusha slavery and logistical seizure. This condition fulfills the elements of mass deception. Furthermore, the doctrinal repetition of the slogan is a form of linguistic coercion that exploits power asymmetry to castrate the people's critical reasoning. In conclusion, the invasion of Japanese fascism in Indonesia did not only take place through military equations, but also through a cognitive dictatorship based on language fabrication. This study is relevant as a historical mirror for detecting the anatomy of structural lies in the contemporary post-truth era.